VD_FINDINFO Jug / 2016 / 123 vom 26. Mai 2015 - VD Tribunal cantonal (2015)
ENLÈVEMENTINFRACTION, LOI FÉDÉRALE SUR LES ÉTRANGERS, RETRAITVOIE DE DROIT | 183 CP, 116 al. 1 let. a LEtr, 386 al. 2 let. a CPP (CH)